Urbanization, climate change, and structural transformation in Accra, Ghana - Michael Danquah; Bazoumana Ouattara; Williams Ohemeng; Alfred Barimah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines the effect of climate on citywide labour productivity in the Accra city region. We use data from Ghana's Integrated Business and Establishment Survey dataset, climate data at the sub-city level from Ghana Meteorological Agency, and satellite and reanalysis data, as well as key informant interviews with representatives of enterprises and city authorities and officials of the National Disaster Mobilization Agency, for this exercise. The findings show that rainfall, which contributes substantially to vulnerability and risk in the city, significantly reduces labour productivity, while the effect of temperature is not significant. This is an indication of the detrimental effect of rainstorms and floods on firm productivity and the growth of highproductivity sectors in the city. The findings are essential for discussions on the new urban agenda as African cities seek to understand the impact of climate change and how to integrate climate change considerations into urban planning strategies and policies. There is an urgent need for investment in adaptation to mitigate the impacts of climate shocks in order to create a more liveable and sustainable city to facilitate economies of scale, specialization, and thriving highproductivity sectors.
Keywords: O55; Q54; Q58; R11; 330; urbanization; structural transformation; climate; Accra